SOSIALISASI PEMILAHAN DAN PEMANFAATAN SAMPAH ORGANIK DAN ANORGANIK SEBAGAI UPAYA MENUJU ZERO SAMPAH PADA WARGA KELURAHAN ANGGUT BAWAH KOTA BENGKULU - Salaisyah Amalia Yusuf; Salsabila Delfri; Anisa Fiteria; Wevy Efticha Sary (TRIBUTE: JOURNAL OF COMMUNITY SERVICES, 2025)
THE WASTE PROBLEM IN ANGGUT BAWAH SUBDISTRICT BENGKULU CITY IS CHARACTERIZED BY LOW WASTE SORTING PRACTICES AT THE SOURCE AND LIMITED UTILIZATION OF WASTE INTO VALUE-ADDED PRODUCTS. This activity aims to improve residents’ knowledge and skills in sorting organic and inorganic waste and processing it into useful products as an effort toward zero waste based on local wisdom. The implementation methods included material presentation using real samples, demonstrations of waste utilization into compost, eco-enzyme, petasol, ecobricks, and flower pots from used diapers, interactive discussions, household waste potential data collection, as well as evaluation and documentation. Participants consisted of residents from RT 01 to RT 06, applying a participatory approach. The results showed an increase in residents’ understanding of waste classification and processing techniques, indicated by active participation in discussions and interest in independently practicing waste processing. Data collection revealed that household waste was dominated by organic waste from kitchen residues, with limited previous utilization. In conclusion, socialization based on physical demonstrations and local wisdom effectively improved environmental literacy, motivation, and residents’ skills. It is recommended to continue the program through regular training, provision of waste sorting facilities at the RT level, and collaboration with the Environmental Agency.